2012
DOI: 10.1002/adfm.201102196
|View full text |Cite
|
Sign up to set email alerts
|

Thin SnO2 Nanowires with Uniform Diameter as Excellent Field Emitters: A Stability of More Than 2400 Minutes

Abstract: The stability of a field‐emission event, i.e., the stability of the emission current over a long period of time, against thermal effects, etc., is one of the key factors for its application in real devices. Although nanostructures have the advantages of high aspect ratios and faster device turn‐on times, the small masses and large surface areas make them vulnerable to both chemical and physical damages and they have a lower melting point compared to bulk materials of same compositions. SnO2, one of the most at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 57 publications
0
57
0
Order By: Relevance
“…9(b). The β value is lower compared with the reported carbon nanotubes [30], ZnO nanowires [31], ZnS nanowires [32], SnO 2 nanowires [33], WO x nanowires [34,35], B nanowires [36,37], and LaB 6 nanowires [38], but is equivalent to the CdS nanostructure arrays [39] and Fe 2 O 3 columnar arrays [40]. Recently, Chiu et al [5] reported that there is no emission density from SiO 2 nanowires, but good FE properties from platinum coated SiO 2 nanowires.…”
Section: Resultsmentioning
confidence: 86%
“…9(b). The β value is lower compared with the reported carbon nanotubes [30], ZnO nanowires [31], ZnS nanowires [32], SnO 2 nanowires [33], WO x nanowires [34,35], B nanowires [36,37], and LaB 6 nanowires [38], but is equivalent to the CdS nanostructure arrays [39] and Fe 2 O 3 columnar arrays [40]. Recently, Chiu et al [5] reported that there is no emission density from SiO 2 nanowires, but good FE properties from platinum coated SiO 2 nanowires.…”
Section: Resultsmentioning
confidence: 86%
“…One-dimensional (1D) metal oxide nanomaterials such as ZnO [1][2][3], SnO 2 [4,5], WO 3 [6], Fe 2 O 3 [7], and TiO 2 [8][9][10] have stimulated enormous attention for field emitters in the past decades due to their sharp tips, high aspect ratio, and superior antioxidation ability which can operate under unfavorable environment with relatively high oxygen partial pressure in their applications. Among various 1D metal oxide nanomaterials, TiO 2 nanotube arrays (TNAs) fabricated by anodization have attracted considerable attention for several reasons [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, one-dimensional (1D) transition metal oxide nanowires have constituted an important domain of the family of nanostructures, due to their unique structures, intriguing properties and potential applications, which differ from those of the corresponding bulk-state materials [1][2][3][4][5]. Tricobalt tetraoxide Co 3 O 4 , a p-type semiconductor, has attracted a growing interest owing to its wide range of application in catalytic reaction, lithiumion batteries, gas sensors, and supercapacitors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%